Output-Feedback Tracking Control for Polynomial Fuzzy-Model-Based Control Systems - Lam, H. K.; Hongyi Li (IEEE transactions on industrial electronics (1982), 2013)
This paper presents the output-feedback tracking control of the polynomial fuzzy-model-based control system which consists of a polynomial fuzzy model representing the nonlinear plant and an output-feedback polynomial fuzzy controller connected in a closed loop. The output-feedback polynomial fuzzy controller is employed to drive the system states of the nonlinear plant to follow those of a stable reference model subject to an H ∞ performance. Based on the Lyapunov stability theory, sum-of-squares-based stability conditions are obtained to determine the system stability and facilitate the control synthesis. A feasible solution can be found numerically using the third-party Matlab toolbox SOSTOOLS. Simulation results are provided to demonstrate the merits of the proposed control approach.